From the Editors - Burkiewicz, Łukasz (Perspektywy Kultury, 2022)
The recent issue of Perspectives on Culture have been much larger than those published in previous years. This is primarily due to the growing interest in publishing in our journal and the associated large number of submitted texts on a high scientific level. In order to enable the largest possible group of authors to publish, we have decided to increase the number of texts in subsequent issues of our journal.The main theme section of this issue under the guest editorship of Prof. Agnieszka Januszek-Sieradzka, PhD, has been titled “The Court of the Queen in the Middle Ages and in the Modern Era – People, Relationships, Influences.” This section is presented in the introduction by the Professor herself. Let me add that the section contains nine articles written by authors from various research centers in Poland.